Application “Pentol Bakar (Pencet Tombol Bila Ada Kegawatdaruratan Jiwa)” As an Innovation of RSJID Dr. Aminogondohutomo - Widyaningtyas, Ryka; Dwidiyanti, Meidiana (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Based on WHO data in 2019, every 8 people or around 970 million people worldwide. The problem of mental disorders is a complex issue while in Indonesia access to services is limited so that to optimise health services innovation is needed, especially in digital technology. This study aims to determine how the analysis of the use of the pentol bakar application at RSJD Dr. Amino Gondohutomo along with SWOT analysis. (Strengths, weaknesses, opportunities, threats). The literature search method in this study is a scoping review using the PCC framework to create journal inclusion and exclusion criteria and PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews). The results of this research review are 5 articles that match the research topic from 893 articles. The Pentol Bakar application made by RSJD Dr.Amino Gondohutomo has advantages in the form of easy access for patients and families and helps health services more efficiently because of a faster response. While the shortcomings in using the application are in the form of a lack of information and understanding related to the application used. SWOT analysis conducted by researchers can provide recommendations in the future in using the application so that it is more effective. These findings are expected to make a positive contribution in improving the quality of mental health services in related institutions.